(untitled) (Pesquisa Odontológica Brasileira, 2001)
Glass ionomer cements are important options in restorative and preventive dentistry due to their adhesion to the tooth surface and to fluoride release, which can decrease the risk of recurrent caries. The topical use of acidulated and neutral fluoride gels has been frequent in dentistry. However, this procedure can adversely affect the surface of restorative materials, increasing their roughness and the retention of dental plaque. Thus, this study evaluated the period in which Vitremer glass ionomer cement maintains its antimicrobial activity over Streptococcus mutans ATCC 25175, as well as the effects of topical application of acidulated and neutral fluoride gels on these microbiological parameters and on the superficial characteristics of the restorative material. It was verified that the antimicrobial activity of Vitremer is very transient, decreasing to an undetectable level after four days, and the topical application of fluoride gel did not restore this activity. It was observed that S. mutans ATCC 25175 adheres to this restorative material, and the topical fluorides did not affect this event. The surface of Vitremer was not altered by the application of fluoride gels.